2003
DOI: 10.1177/13674935030074004
|View full text |Cite
|
Sign up to set email alerts
|

Drug Errors: What Role do Nurses and Pharmacists have in Minimizing the Risk?

Abstract: A multi-professional project was carried out in order to identify the interventions that nurses and pharmacists make in relation to drug administration (an intervention refers to 'the process of querying a prescription with a prescriber'). The project highlights the importance of both these occupational groups in identifying prescribing errors and preventing them from being translated into actual medication errors. It also identifies the need for adequate training for nursing and medical staff, along with syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…This is higher than reported in most studies which found an incidence ranging from 0.2% to 1.28%,2123 with one study describing a higher incidence of 5.6% 7. None of the studies mention any harmful effects on the patients, probably because the errors were corrected prior to administration 15…”
Section: Discussioncontrasting
confidence: 56%
“…This is higher than reported in most studies which found an incidence ranging from 0.2% to 1.28%,2123 with one study describing a higher incidence of 5.6% 7. None of the studies mention any harmful effects on the patients, probably because the errors were corrected prior to administration 15…”
Section: Discussioncontrasting
confidence: 56%
“…Condren et al [24] reported that during 12 months 91% of 4605 interventions performed for 3978 patients were accepted by the physicians. A lower acceptance rate of 80% was reported in a study by Guy et al [25]. These findings demonstrated that reasonable suggestions provided by clinical pharmacists are generally accepted by physicians.…”
Section: Discussionmentioning
confidence: 65%
“…Several studies have confirmed that doses errors are medication errors most encountered in pediatrics. [6333435363738394041] In the study of Folli et al . [2] carried out in two children's hospitals, overdose was the most encountered dose error, and antibiotics were the most concerned by this DRP.…”
Section: Discussionmentioning
confidence: 99%